Elevated Asymmetric Dimethylarginine is Associated With Oxidant Stress Aggravation in Patients With Early Stage Autosomal Dominant Polycystic Kidney Disease - Vassilios Raptis; Panagiotis I. Georgianos; Pantelis A. Sarafidis; Athanasios Sioulis; Kali Makedou; Areti Makedou; Dimitrios M. Grekas; Stergios Kapoulas (Karger Publishers, 2014)
Background/Aims: In experimental models of polycystic kidney disease impaired bioavailability of nitric oxide (NO) and elevated mRNA expression of oxidative stress markers at the kidney level was noted. However, clinical studies investigating the potential role of endothelial dysfunction and oxidative stress in the pathogenesis of autosomal dominant polycystic kidney disease (ADPKD) are limited. We evaluated asymmetric dimethylarginine (ADMA) as marker of NO synthase inhibitor as well as 15-F2t-Isoprostane and oxidized-low density lipoprotein (oxidized-LDL) as measures of oxidative stress in patients with early stages ADPKD. Methods: We recruited 26 ADPKD patients (Group A) with modestly impaired renal function (eGFR 45-70 ml/min/1.73m2), 26 age- and sex-matched ADPKD patients (Group B) with relatively preserved renal function (eGFR)>70 ml/min/1.73m2), and 26 age- and sex-matched controls (Group C). Determination of circulating levels of ADMA, 15-F2t-Isoprostane, oxidized-LDL and routine biochemistry was performed. Results: Group A and B had significantly higher ADMA levels as compared to controls (1.68±0.7 vs 0.51±0.2 μmol/l, P2t-IsoP and oxidized-LDL levels were also significantly higher in Group B relative to controls (788.8±185.0 vs 383.1±86.0 pgr/ml, P2t-Isoprostane (r=0.811, PConclusion: This study shows elevation in circulating levels of ADMA along with aggravation of oxidative stress from the early stages of ADPKD.